A Pack of Predators - Soper, S. I. 1929- (Thorndike, ME: Center Point Large Print, 2020)
At thirty-five, Federal Marshal Buck Fyffe has had eleven years experience as a lawman. When he and Deputy Steve Larson were charged with taking the outlaw Luther Gibbs to the newly established Yuma Territorial Prison, he wasnt expecting any problems. But when Larson gets snake bit and dies, Fyffe finds himself almost three days away from the Yuma prison with no one to spell him while he sleeps.
Keywords: Arizona Territorial Prison -- Fiction; United States marshals -- Fiction; Marshals -- Fiction; Outlaws -- Fiction; Yuma (Ariz.) -- Fiction; West (U.S.) -- Fiction; Western fiction